Transformasi Lagu “Kacang Dari” ke Dalam Chamber Music - Komang Wira Adhi Mahardika; Hendra Santosa; Ni Wayan Ardini (Gondang: Jurnal Seni dan Budaya, 2020)
This article aims to reveal the transformation process of a traditional lullaby entitled Kacang Dari into chamber music so that the song can rise from the of extinction. The problems discussed in this article are focused on the rapid development of technology that has indirectly made the legacy of traditions, especially traditional songs, increasingly abandoned. One of the traditional songs that is on the verge of extinction is Kacang Dari. Kacang Dari is a traditional song originating from Pujungan Village, Pupuan, Tabanan-Bali. This song is a lullaby that is rarely sung now, even very few children in Pujungan Village know about the song Kacang Dari. In order to approach this problem, the researcher uses the theory of transformation and composition theory to represent the song into a new form, namely chamber music. In this transformation process the researcher uses the creation method which refers to the method offered by Alma Hawkins consisting of the exploration, improvisation, and formation stage. This creation concludes that a traditional song that is getting extinct and not sung by the song can be picked up and transformed into a new form so that it can maintain its existence and attract the public's interest to be able to re-enjoy the song.